Inhibition of Mineralization of Urinary Stone Forming Minerals by EDTA Salts and Effect of Marco and Micro Nutrient Metal Ions on the Inhibition - Rao, T.V.R.K.; Das, Maitreyee (Asian Journal of Chemistry, 2010)
Disodium, dipotassium and magnesium salts of ethylenediamine tetraacetic acid (EDTA) have been studied as inhibitors in the mineralisation of urinary stone forming minerals, viz., calcium phosphate, oxalate or carbonate. Inhibition efficiency has been studied in different experimental models. Effect of some macro- and micro-nutrient metal ions on the inhibition efficiency of disodium EDTA has also been investigated. Utility of the results in urolithiasis inhibition has been discussed.